Bases teóricas y práctica pedagógica del docente para el aprendizaje del cuidar/cuidado en estudiantes de enfermería - Jara Huayta, Iris (2015)
Summary this research is a descriptive, exploratory qualitative approach. The main purpose was to describe and analyze the theoretical bases and teaching practice of teachers. The theoretical approach was based on the thought of Freire, Demo and Waldow. The participants were 10 teachers. For data collection, interview technique was applied to depth and observation. Applied analysis of content and documentary technique; of which emerged: category i. theoretical Bases of the pedagogical process applied by the teacher; distinguishing two sub categories: dominance of the behaviourist approach and divergence between the constructivist approach to curriculum of study and focus Behaviorism the teacher in the learning process, category II. Strategies in teaching practice of teachers; where were identified the subcategories: prior experiences and motivation, developing content, scenarios of practice with the themes: learning caring / care: simulated laboratories, institutions of health and Comunidad-Familia, methodological strategies and resources didacticosy category III. Ethics in the learning of the student, with the themes: learning to care / care taking into account values, respecting the user and with warmth. Final considerations determined that on findings, it became apparent that the theoretical bases and pedagogical practices of teachers, is focused on a traditional behavioral pedagogy, with positivist thought. In the development of theory and practice, the teacher encourages rote learning, repetition and favors the learning of procedures. Predominance of the behaviorist approach, structured linear receptive and repetitive classic with trend biologista-functionalist logical rationalism, teacher-centred is evident. She is evidencio divergence between the constructivist approach of curriculum study model by competencies and focus Behaviorism the teacher with objectives behavioural-technicist reflecting characteristic of a curriculum model biologizante